2000
DOI: 10.1080/089419300750059343
|View full text |Cite
|
Sign up to set email alerts
|

Liver Bridging Techniques in the Treatment of Acute Liver Failure

Abstract: The introduction of orthotopic liver transplantation in the management of acute liver failure has dramatically increased the survival rates of patients at the cost of removing the patient's native liver and life-long dependence on immunosuppression. However, it is well known that in many patients with acute liver failure the diseased liver has the potential to recover. Death in these patients is often due to increased intra-cranial pressure or infection. Liver bridging techniques are assigned to temporarily pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Recent studies have shown that extracorporeal liver support systems could temporarily support patients' liver function, improve their preoperative condition, and enhance their tolerance to surgery, thus extending the waiting time for a donor liver as a bridge to LT [12][16].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that extracorporeal liver support systems could temporarily support patients' liver function, improve their preoperative condition, and enhance their tolerance to surgery, thus extending the waiting time for a donor liver as a bridge to LT [12][16].…”
Section: Discussionmentioning
confidence: 99%